KEADILAN DALAM IMPLEMENTASI KEBIJAKAN PROGRAM PEMELIHARAAN KESEHATAN MASYARAKAT SURAKARTA (PKMS) DI KOTA SURAKARTA - , DIAN HIDAYAH, Dr. Ambar Widaningrum, MA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Many people in Indonesia did not understand the importance of having health insurance. Most of beneficiaries of health insurance came from middle class or above, while the poor used medical treatment. However, Jamkesmas itself has not worked properly effective, there are still many poor peopledid not covered enough in the Jamkesmasprogram. Concerning the problem of resident who did not have health insurance at all, Surakarta City Government held a health insurance program called PemeliharaanKesehatanMasyarakat Surakarta (PKMS). PKMS is the provision of healthcare that cover promote, preventive, curative, and rehabilitativeservice. The beneficiaries of PKMS program is the qualified community in Surakarta. PKMS program comprises into two parts, there are Gold and Silver PKMS, whom PKMS Gold is addressed for poor people and PKMS Silver addressed to people who has no insurance coverage. Researchers wanted to observe the implementation of the program PKMSfrom the perspective of equity. This research was conducted in Surakarta using a contextual and interpretative analysis. Researcher describes the implementation PKMS from the angle of equity. Theresearchabout implementation of the PKMS program concludes fair. This can be seen from the services provided by the PKMS and the health center / hospital associated to PKMSparticipants. It is also, compared to Jamkesmas program hospital claims, there is no problem in PKMS about hospital claims.